Tadpole buccal secretory glands as new support for a Neotropical clade of frogs - Giaretta, Ariovaldo A.; de Freitas, Felipe G.; Antoniazzi, Marta M.; Jared, Carlos (Zootaxa, 2011)
Phylogenetic hypotheses of species of Leptodactylus have been proposed but relationships often consider few species and high-level groups are supported by few, homoplasious morphological characters. Similarities between the reproductive biology of species of the L. marmoratus (formerly Adenomera) and those of the L. fuscus group may represent homoplasies or, as previously suggested, shared derived features pointing to their closer relationship. We determined the presence of buccal foaming glands in tadpoles of three species of Leptodactylus (L. furnarius, L. labyrinthicus and a member of the L. marmoratus group) by histological preparations. The presence of these glands and other seven characters were mapped onto two alternative topologies in order to understand the relationships among Leptodactylus species groups and the evolution of their reproductive features. Two sets of foaming glands were found in all species studied: 1) rows of secretory ridges and 2) secretory pits. Mapping the nine characters on the currently recognized phylogeny (emphasizing closer relationship among L. latrans, L. fuscus and L. labyrinthicus) resulted in sixteen steps (CI = 56; RI = 22); in the alternative hypothesis (closer relationship between L. marmoratus group and Leptodactylus of the L. fuscus groups) it resulted in eleven steps (CI = 82; RI = 78). Our evidences support that species in the L. marmoratus group are not the sister group to the remainder of Leptodactylus, but probably a subset of the L. fuscus group.